1999
DOI: 10.1021/jp991025r
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of 1,3-Dioxolane:  Kinetic, Mechanistic, and Modeling Study of OH Radical Initiated Oxidation

Abstract: An absolute rate pulse radiolysis technique was used to measure k(OH + 1,3-dioxolane) ) (8.8 ( 0.9) × 10 -12 cm 3 molecule -1 s -1 at 295 K in 1000 mbar of Ar. Relative rate techniques were used to study the reactions of OH radicals and Cl atoms with 1,3-dioxolane and Cl atoms with ethylene carbonate and methylene glycol diformate at 300 K in 1 bar of synthetic air. Rate coefficients were k(OH + 1,3-dioxolane) ) (1.04 ( 0.16) × 10 -11 , k(Cl + 1,3-dioxolane) ) (1.6 ( 0.3) × 10 -10 , k(Cl + ethylene carbonate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…The sole cycloalkoxy radical produced during the atmospheric oxidation of 1,3,5-trioxane also undergoes CÀO bond cleavage rather than reaction with O 2 [8] and is thus consistent with the high strain energy of this triether ( % 30 kJ mol À1 ). In contrast, Sauer et al [7] reported that the cycloalkoxy radical generated by H-atom abstraction from the ÀOCH 2 OÀ group in 1,3-dioxolane preferentially reacts with molecular oxygen to form a cyclic carbonyl compound, despite having an estimated ring strain energy of around 30 kJ mol À1 . This is the only instance where reaction with O 2 appears to be a favourable reaction pathway for the highly strained C 5 cycloalkoxy radicals.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The sole cycloalkoxy radical produced during the atmospheric oxidation of 1,3,5-trioxane also undergoes CÀO bond cleavage rather than reaction with O 2 [8] and is thus consistent with the high strain energy of this triether ( % 30 kJ mol À1 ). In contrast, Sauer et al [7] reported that the cycloalkoxy radical generated by H-atom abstraction from the ÀOCH 2 OÀ group in 1,3-dioxolane preferentially reacts with molecular oxygen to form a cyclic carbonyl compound, despite having an estimated ring strain energy of around 30 kJ mol À1 . This is the only instance where reaction with O 2 appears to be a favourable reaction pathway for the highly strained C 5 cycloalkoxy radicals.…”
Section: Discussionmentioning
confidence: 94%
“…In the absence of authentic reference spectra for 3-oxopropyl formate or 2-oxoethyl formate it is not possible to confirm this. Although the formation of these formates cannot be ruled out, they are highly unlikely to be major products since attack at the ÀOCH 2 OÀ site is only expected to contribute less than 20 % to the overall reactivity of 1,3-dioxane, [4,7] . A number of reaction parameters were varied during the set of experiments, as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations